Wintering : the power of rest and retreat in difficult times ([s.l.] : Penguin Random House, 2020)
Wintering is a poignant and comforting meditation on the fallow periods of life, times when we must retreat to care for and repair ourselves. Katherine May thoughtfully shows us how to come through these times with the wisdom of knowing thad, like the seasons, our winters and summers are the ebb and flow of life.
Keywords: Zelfontplooiing